Integrated bioprocessing of cassava residues for enzymatic starch recovery, citric acid production, and effluent detoxification - Suleiman Adebisi Olaniyan; Jelili Babatunde Hussein; Moruf Olanrewaju Oke; Bolanle Aishat Akinwande; Tilahun Seyoum Workneh; Maria Ayodele; Isaac Adebayo Adeyemi (Scientific Reports)
Abstract Waste management and effluent treatment in bio-procedures are essential for maintaining a clean environment and enhancing the value of cassava waste. The study analysed effluents for biochemical oxygen demand (BOD5) content and cyanide concentration (HCN), using activated charcoal, sand, and gravel as filter media. It also evaluated the enzymatic production of starch from cassava peels and fermentation with Aspergillus niger for citric acid production. The charcoal filtration got rid of the most pollutants, dropping BOD5 from 2467 mg/L to 393 mg/L (84.07%) and HCN from 3.63 mg/L to 0.43 mg/L (88.15%), but these levels were still higher than the international standards for discharge. When used together, cellulase and pectinase were able to extract up to 5.30 g of starch from dry cassava peel, which was more than what was possible with single enzymes or control treatments. Yield increased significantly with longer extraction times, as 3-hour extractions yielded more starch than 2-hour treatments, confirming a time-dependent effect. The study found that starch from Lekmauck Cantonment Processing Centre (LMC) and Ile Ileri Processing Centre (IIO) samples showed superior paste stability and higher peak viscosities compared to native starch and Adekunle Fajuyi Cantonment Processing Centre (AFC) samples. Fermentation trials showed optimal citric acid yields with 3% and 4% methanol, reaching 1.41 g/L (IIO) at 3% and 1.42 g/L (IIO) at 4%, respectively. However, yields plateaued beyond 3%, suggesting possible metabolic inhibition. The study concluded that cassava waste can be effectively recycled for local consumption and industrial use, thereby reducing environmental impact and promoting sustainable development.